QUESTIONING THE ROLE OF ADAT CRIMINAL LAW IN INDONESIA’S CRIMINAL CODE REFORM: A POST-KUHP 2023 PERSPECTIVE - Hermanto, Bagus; Putra, Rengga Kusuma; Nugroho, Aziz Widhi; Hattori, Mariko; Yusa, I Gede; Ardani, Ni Ketut (Faculty of Law Sriwijaya University, 2025)
The enactment of Law Number 1 of 2023 concerning the New Indonesian Criminal Code (KUHP 2023) marks a significant shift in Indonesia’s legal landscape, particularly concerning the recognition and integration of Adat Criminal Law within the national legal framework. This study explores the future prospects of Indonesia’s criminal law reform, focusing on the coexistence of statutory and customary law, judicial application of adat norms, human rights considerations, local governance roles, public perception, and policy directions. Using a normative juridical approach, the research examines the legal, sociological, and political justifications for adat law recognition, its challenges in enforcement, and the implications for Indonesia’s legal pluralism. Key findings highlight the complexities of judicial discretion in applying adat law, the need for harmonization with constitutional protections, and public attitudes toward adat-based justice mechanisms. Additionally, this study proposes policy recommendations for ensuring legal certainty, judicial training, and technological advancements in adat law documentation. By addressing these challenges, Indonesia can establish a balanced legal system that respects customary traditions while aligning with national and international legal standards.